2017
DOI: 10.4103/asl.asl_87_17
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects of artemisia species: A systematic review

Abstract: Background:Over the last century, human life style and food habits have drastically changed which lead to various chronic diseases. Diabetes mellitus is one such disease which is causing serious problems to human health. Allopathic drugs are not much effective in handling the disease and its complications. Hence focus has been turned towards the traditional system of medicine. Medicinal plants play an important role in the management of diabetes mellitus.Methods:Experimental studies conducted on species of Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Some studies have shown that plant species of the Artemisia genus, used in the ethnomedical systems of Asia, have antidiabetic properties (Dabe and Kefale, 2017 ). The people living in the territory of present-day Northern Asia or Siberia, widely used Artemisia extracts for the treatment of diabetes-like conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that plant species of the Artemisia genus, used in the ethnomedical systems of Asia, have antidiabetic properties (Dabe and Kefale, 2017 ). The people living in the territory of present-day Northern Asia or Siberia, widely used Artemisia extracts for the treatment of diabetes-like conditions.…”
Section: Discussionmentioning
confidence: 99%
“…(Tan et al, 1998 ; Bora and Sharma, 2011 ; Abad et al, 2012 ; Ivanescu et al, 2015 ; Pandey and Singh, 2017 ). It was observed that the various Artemisia aqueous and alcoholic extracts possessed an antidiabetic effect caused by hypoglycaemic action (Dabe and Kefale, 2017 ). Pharmacological data provides convincing evidence that the extracts of A. absinthium (Daradka and Abas, 2014 ), A. afra (Afolayan and Sunmonu, 2011 ), A. amygdalina (Ghazanfar et al, 2014 ), A. dracundulus (Ribnicky et al, 2006 ), A. judaica (Nofal et al, 2009 ), A. herba-alba (Awad et al, 2012 ), A. ludoviciana (Anaya-Eugenio et al, 2014 ), and A. sphaerocephala (Xing et al, 2009 ) were effective in streptozotocin- and alloxan-induced hyperglycemia experimental animal models due to their significant ability to reduce blood glucose level and protect against metabolic aberrations caused by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In Western and African folk medicine, several species of the genus Artemisia are used for their claimed healing properties and for the cure of specific ailments. The early in vitro antiobesity-effects [ 135 ] of Artemisia could be due to the presence of active compounds, such as terpenes, steroids, and saponins, and also the active ingredients, such as tannins and flavonoids [ 136 ]. Physalis alkekengi , also referred to as ground cherry, is an indigenous herb in Iran and many other regions of Asia such as China.…”
Section: Anti-obesity Properties Of Polyphenolsmentioning
confidence: 99%
“…The result of this vast investigation showed the Artemisia species (extracts and essential oils) as exhibiting antiparasitic, anticancer and anti-inflammatory action in addition to antioxidant, wound healing, antinociceptive, immunoregulation, hepatoprotective, neuroprotective, anti-asthmatic, antidiabetic, antihypertensive, anti-adipogenic, anti-ulcerogenic, antiviral, antibacterial, antifungal, and anti-osteoporotic activities [ 10 , 11 , 12 , 13 , 18 , 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%